2022
DOI: 10.1108/jica-02-2022-0018
|View full text |Cite
|
Sign up to set email alerts
|

Does a discharge to assess programme introduced in England meet the quadruple aim of service improvement?

Abstract: PurposeThis paper intends to examine and evaluate the implementation and delivery of a discharge to assess pathway based on the UK Department of Health and Social Care Hospital Discharge Policy in relation to the quadruple aim of healthcare improvement: improving patient experience, reducing costs, benefiting the wider population and improving the work life of staff.Design/methodology/approachUsing a place based partnership in the south of England, 18 staff involved the delivery of discharge to assess and four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The post-2020 evidence regarding the national policy’s impact is limited, but it does suggest variations in approaches, emphasising the importance of single access points, integrated teams, and the need for increased community capacity, 7 all of which were echoed by this study. Additionally, the study’s pilot project 8 found benefits in terms of staff satisfaction and working conditions however these were not strong themes in this current study.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The post-2020 evidence regarding the national policy’s impact is limited, but it does suggest variations in approaches, emphasising the importance of single access points, integrated teams, and the need for increased community capacity, 7 all of which were echoed by this study. Additionally, the study’s pilot project 8 found benefits in terms of staff satisfaction and working conditions however these were not strong themes in this current study.…”
Section: Discussionmentioning
confidence: 61%
“…They suggested that the funding of care for the initial post discharge period was helpful, partnership working enabled good relationships, adaptability of workforce was present and that systems were less risk averse than before. In addition, the pilot study to this project, 8 which focused on the experiences of hospital staff, showed benefits to the quadruple aims of healthcare improvement (improved quality, efficiency, wider health benefit and staff satisfaction 9 ), particularly around staff satisfaction and working conditions with staff reporting enhanced autonomy and widening skill sets.…”
Section: Introductionmentioning
confidence: 99%